To study the GenZ's awareness about private equity market, a wealth growth option in Bhopal & Ahmedabad. - Nandani Jagad; Nupur Shrivastava; Jignesh Vidani (Journal of Advanced Research in Accounting and Finance Management, 2026)
The study aims to analyse the level of awareness and perception of private equity as an investment option among individual investors. A structured questionnaire was used to collect responses from 154 participants through a purposive sampling method. The data were analysed using SPSS software, employing descriptive statistics, reliability tests, and chi-square tests to identify associations between demographic factors and investment awareness. The results revealed that while most respondents are highly familiar with traditional investment avenues such as bank fixed deposits, mutual funds, and gold, the awareness of private equity remains relatively low. However, respondents who are financially literate and professionally engaged in finance or business sectors show comparatively higher understanding and interest in private equity. The reliability analysis (Cronbach’s alpha = 0.938) indicated strong internal consistency of the questionnaire. Crosstab results suggested significant associations between demographic variables such as age, education, and occupation with awareness and risk perception toward private equity. The study concludes that there is a growing yet limited awareness of private equity among Indian investors, emphasising the need for investor education and financial inclusion initiatives to broaden investment perspectives beyond conventional options.